"Crack, nem pensar": um estudo sobre mídia e política criminal - Böes, Guilherme Michelotto (2011)
From 2009 and 2010, the leading media group of state Rio Grande do Sul, has built a campaign with scathing images of the narcotic substance crack users. Confronting this proposal from the media to perform its debate on the crack based on studies on this substance, are on damage reduction is as critical of criminal law, we intend to present this work that is analysis of the media as object and means of interaction and cultural background. This researches presents, for as short a deconstitution, with various ― "theoretical lines", several authors for various doctrinal conceptions, without being unique, so as not to limit these theoretical perspectives, as well as their limitations. With the analysis of the proposed campaign, we seek to make an analysis of social ― "theory" media, so that, we could have the same as a product of cultural interaction. Also not to deny the importance of media in a democratic state, it took a brief consideration of the shape of a democratic state. Avoid presenting more a debate on drug policy, not to sustain the discourse that is now done and repeated, both in the academic, as policy makers. This discourse on national drug policies is widely debated at academic, and demonstrate overshadowed by the media campaign, because it allows openly wrong one, and exclusive taxation, especially as users, maintaining the prohibitionist argument, operating in a private political context. In this vein, we present a critical analysis, but without using or join a critical criminology, but a Cultural Criminology. The cultural work is the engagement of ― "negotiation" between identities and their meanings: its symbols, the roots of crime and deviance, in order to find a collective solution. Assumed greater awareness of social values in an attempt to present tensions and / or failures of policies of inclusion and exclusion.